Clinical evaluation of automated capillary refill time estimation in dogs and cats - Cugmas, Blaž; Štruc, Eva; Spīgulis, Jānis (SPIE, 2019)
In this study, we clinically evaluated a pulse oximeter-based device for automated capillary refill time (CRT) estimation in dogs and cats. CRT can reveal conditions like shock or anemia in dogs and cats. However, visual CRT estimation has low repeatability, and the available optical systems for automated estimation are not suitable for pets. We evaluated a custom-made portable CRT measuring device on various measurement sites of 12 dogs and 11 cats with parallel visual CRT estimation on the gum by treating veterinarian. The capillary refill was also recorded by a video camera for reference. The visual and video procedures were moderately correlated with the coefficient of 0.61; visual CRT values were on average for 0.18 s longer than the reference. On average, ~32% of measurements with the proposed device were successful. The rest failed due to excessive pigmentation, motion artifacts, and other pressure-induced effects. The measurement sites of the metacarpal pad, digit, and tail were moderately correlated with the reference values with coefficients of 0.53, 0.58, and 0.42, respectively.
Keywords: Capillary refill time; capillary refill test; dogs; cats; microcirculation; pulse oximeter; photoplethysmography; Research Subject Categories::NATURAL SCIENCES::Physics::Atomic and molecular physics